Imperfect Reworking Process Consideration in Integrated Inventory Model under Permissible Delay in Payments. (13th May 2008) - Lo, Ming-Cheng; Yang, Ming-Feng
Abstract : This study develops an improved inventory model to help the enterprises to advance their profit increasing and cost reduction in a single vendor single-buyer environment with general demand curve, adjustable production rate, and imperfect reworking process under permissible delay in payments. For advancing practical use in a real world, we are concerned with the following strategy determining, which includes the buyer_s optimal selling price, order quantity, and the number of shipments per production run from the vendor to the buyer. An algorithm and numerical analysis are used to illustrate the solution procedure.